BURNOUT PADA PERAWAT DITINJAU DARI EFIKASI DIRI DAN DUKUNGAN SOSIAL DI RUMAH SAKIT âXYZâ DI SURAKARTA (Nurses Burnout in terms of Self Efficacy and Social Support at âXYZâ Hospital of Surakarta) - Lailani, Fereshti; Rifayani, Hastuti; Paramita, Metta (TALENTA, 2014)
The research was aim to find out the relationship between self-efficacy and social support with burnout among nurses. Proposed hypotheses were as followed: 1). burnout correlatedÂ  withÂ  self-efficacyÂ  danÂ  socialÂ  support,Â  2).Â  Self-efficacyÂ  negativelyÂ  correlated with burnout, the lower self-efficacy was, the higher was the burnout; 3) social support negativelyÂ  correlatedÂ  withÂ  burnout,Â  theÂ  higherÂ  socialÂ  supportÂ  was,Â  theÂ  lowerÂ  wasÂ  the burnout.Â  ThisÂ  researchÂ  alsoÂ  createÂ  aÂ  newÂ  modelÂ  ofÂ  competenciesÂ  inÂ  aÂ  wayÂ  toÂ  copeÂ  the burnout happened, considered to nurses work load. TheÂ  subjectÂ  ofÂ  theÂ  researchÂ  consistedÂ  ofÂ  94Â  nursesÂ  ofÂ  âXYZâÂ  HospitalÂ  of Surakarta. Data was collected through questionnaire method using burnout scales, self efficacy scales and social support scales.Â  Statistical method used regression analysis with SPSS for Windows11.5.TheÂ  resultsÂ  showedÂ  thatÂ  thereÂ  wasÂ  significantÂ  correlationÂ  betweenÂ  self-efficacy and social support with burnout (R= 0.743, F= 56.209, p < 0.05) and it contributed as much as 55.3Â  %.Â  Self-efficacyÂ  hadÂ  significantlyÂ  negativeÂ  correlationÂ  withÂ  burnoutÂ  (t=Â  -6.250 , p < 0.05). Social support also had significantly negative correlation with burnout (t= -3.106 , p<0.05).Key words: self-efficacy, social support, burnout